2020
DOI: 10.5382/econgeo.4714
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Hydrothermal Alteration Intensity in Volcanic-Hosted Massive Sulfide Systems Using Portable X-Ray Fluorescence Analysis of Drill Core: An Example From Myra Falls, Canada

Abstract: Current portable X-ray fluorescence (pXRF) technology can rapidly and inexpensively yield concentrations of geologically significant elements, typically with instrument detection limits below several tens of parts per million. Based on conventional XRF whole-rock geochemical data, both the Ishikawa alteration index and the chlorite-carbonate-pyrite index increase with proximity to sulfide mineralization at Myra Falls. However, available pXRF technology is typically unable to detect all the elements required to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…360-335 Ma) within a transient transtensional intra-continental pull-apart basin generated on the South Portuguese Zone during the geodynamic evolution leading to the growth of the Variscan orogen in the late Paleozoic . Crustal thinning and magmatic intrusion triggered the hydrothermal circulation responsible for the massive sulfide mineralizing events Oliveira et al, 2004;Mitjavila et al, 1997;Tornos, 2006). A detailed review of the geology and mineralization processes of the IPB can be found in , Leistel et al (1998), Carvalho et al (1999), andTornos (2006) and is briefly summarized in Sect.…”
Section: Vms Deposits In the Iberian Pyrite Beltmentioning
confidence: 99%
See 1 more Smart Citation
“…360-335 Ma) within a transient transtensional intra-continental pull-apart basin generated on the South Portuguese Zone during the geodynamic evolution leading to the growth of the Variscan orogen in the late Paleozoic . Crustal thinning and magmatic intrusion triggered the hydrothermal circulation responsible for the massive sulfide mineralizing events Oliveira et al, 2004;Mitjavila et al, 1997;Tornos, 2006). A detailed review of the geology and mineralization processes of the IPB can be found in , Leistel et al (1998), Carvalho et al (1999), andTornos (2006) and is briefly summarized in Sect.…”
Section: Vms Deposits In the Iberian Pyrite Beltmentioning
confidence: 99%
“…From oldest to youngest, these are the (1) Phyllite-Quartzite Group (PQ), (2) the Volcanic Sedimentary Complex (VSC), which hosts the mineralization, and (3) the Culm Group or Baixo Alentejo Flysch Group. The host VSC consists of a complex bimodal volcanic and shallow intrusive sequence of mantle-derived mafic magmas and crustal felsic magmas, interbedded with mudstone and minor chemical sediments (mainly chert and Fe-Mn-rich sediments) (Munhá, 1983;Mitjavila et al, 1997;Thiéblemont et al, 1998;Tornos, 2006). The VSC in the northern area of the IPB -where the Aguas Teñidas deposit is located (Fig.…”
Section: Vms Deposits In the Iberian Pyrite Beltmentioning
confidence: 99%
“…Thus, efforts have been devoted to implementing the use of portable XRF as a fast, costeffective first-stage tool in lithogeochemical exploration in VMS and other mineral systems (e.g. VMS systems, Ross et al, 2014Ross et al, , 2016McNulty et al, 2018McNulty et al, , 2020; komatiite-hosted nickel sulphide deposits, Le Vaillant et al 2014; Au in greenstone belts, Glazley et al, 2011;laterites, Duee et al, 2019), analysing varied materials such as rocks, soils or tills (e.g. Hall et al, 795 2016).…”
Section: Portable Xrfmentioning
confidence: 99%
“…Therefore, alternative ratios using more robust elements have been proposed to track hydrothermal alteration during exploration by p-XRF in VMS system. For instance, the Rb/Sr ratio is suggested to approximate the behaviour of the Alteration Index (McNulty et al, 2020). At Myra Falls, Rb/Sr ratios vary from <0.1 for least altered rocks, 0.1 to 0.5 for weakly altered rocks, 0.5 to 1.0 for moderately altered rocks, 1.0 to 2.0 for 855 strongly altered rocks, and >2.0 for intensely altered rocks (McNulty et al, 2020).…”
Section: Major Elementsmentioning
confidence: 99%
See 1 more Smart Citation